2011
DOI: 10.1002/med.20207
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinases CK1 and CK2 as new targets for neurodegenerative diseases

Abstract: Following the discovery of the human kinome, protein kinases have become the second most important group of drug targets as they can be modulated by small ligand molecules. Moreover, orally active protein kinase inhibitors have recently reached the market and there are many more in clinical trials. The lack of treatments for neurodegenerative diseases has increased human and financial efforts in the search for new therapeutic targets that could provide new effective drug candidates. The importance of kinases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
133
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(135 citation statements)
references
References 161 publications
(171 reference statements)
1
133
0
1
Order By: Relevance
“…CK2 has an array of substrate proteins and functions in diverse cellular processes, including cell growth and proliferation (40,41). Recent studies have also implicated CK2 in neuronal functions and the progression of neurodegenerative diseases (42,43). It has been reported that CK2 phosphorylates several neurodegenerative disease-related proteins, such as ␣-synuclein, synphilin-1, and apolipoprotein E, to enhance aggregate formation (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…CK2 has an array of substrate proteins and functions in diverse cellular processes, including cell growth and proliferation (40,41). Recent studies have also implicated CK2 in neuronal functions and the progression of neurodegenerative diseases (42,43). It has been reported that CK2 phosphorylates several neurodegenerative disease-related proteins, such as ␣-synuclein, synphilin-1, and apolipoprotein E, to enhance aggregate formation (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have highlighted the importance of JNK3 and CK1 isoforms in neurodegenerative diseases (for review, see Resnick and Fennell, 2004;Mehan et al, 2011;Perez et al, 2011). Thus, the dual JNK3/CK1␦ inhibitory activity of indenoquinoxaline derivatives could be useful for application in treatment of conditions such as Alzheimer's disease, where these kinases are implicated in different pathological pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Although all four inhibitors were nontoxic at the concentrations tested in these cells, only the CK1/CK1␦ inhibitor (PF670462) inhibited LPSinduced TNF-␣ production (Table 3). Note, however, that PF670462 has been reported to be a nonspecific MAP kinase inhibitor and can also inhibit JNK (Supplemental Table S2) and p38 MAPK (Perez et al, 2011), both which regulate TNF-␣ production and other proinflammatory cytokines via AP-1 and NF-B transcription pathways (Bhagwat, 2007). Thus, these data provide further evidence for the high degree of specificity and potency of IQ-3 as a JNK inhibitor and suggest the observed inhibition of proinflammatory cytokine production is due to JNK inhibition by this compound rather than to effects on other kinase pathways.…”
Section: Downloaded Frommentioning
confidence: 99%
“…38 Interestingly, CK2 has been linked to oxidative stress-related pathological conditions, such as Alzheimer's disease and PD, and inhibitors of CK2 have been shown to be promising therapeutic agents for the treatment of these diseases. 52 Considering that FAF1 is a substrate of CK2 and nuclear translocation of FAF1 mediates oxidative stress-induced cell death, it is tempting to speculate that the functional interplay between CK2 and FAF1 might have an important role in cell death related to oxidative stress. To address this possibility, further studies are necessary to determine the detailed molecular mechanism of the interaction between CK2 and FAF1 induced by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%